A study on factors that contribute to excellent work culture In Institut Pendidikan Guru Kampus Perempuan Melayu Melaka / Nur Amirah Aidura Tamam and Sofea Mohd Nasir - Tamam, Nur Amirah Aidura; Mohd Nasir, Sofea (2014)
The title of this research is factors that contribute to excellent work culture in Institut Pendidikan Guru Kampus Perempuan Melayu Melaka. The dependent variable for this research is excellent work culture. In this research, there have two independent variables that link with the dependent variable. The two independent variables are work environment and work ethics. For the collection of data, questionnaires and internal data which is directory company was used by the researchers. The researchers was distributed the set of questionnaire to the respondent in the organization. In conducting the research, the researchers was used Statistical Package for Social Science (SPSS) version 21.0. Results showed the two independent variables which are work environment and work ethics contribute to shape the excellent work culture. Both of the independent variables have significant relationships that contribute to shape the excellent work culture in Institut Pendidikan Guru Kampus Perempuan Melayu Melaka.